1994
DOI: 10.1515/revneuro.1994.5.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Characteristics of Fetal Neocortex Transplanted into the Neocortex of Newborn or Adult Rats

Abstract: In humans, the cerebral cortex can be affected by a variety of diseases (vascular, traumatic, neurodegenerative, etc.) and, therefore, several experimental studies have been undertaken to determine to what extent transplantation of cortical neurons could prove a useful treatment for cerebral cortical damage. The purpose of this review is to give an evaluation of the different attempts of neocortical tissue transplantation which have been undertaken, mostly in rodents, during the last decade. First, we examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…As consistently reported in studies dealing with the connectivity of embryonic cortex grafted into newborn hosts, the density of the connections established between thalamus and graft was systematically weaker than that developed between thalamus and intact cortex (Ebrahimi‐Gaillard et al ., 1994; Roger & Ebrahimi‐Gaillard, 1994; Létang et al ., 1997; Gaillard & Roger, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As consistently reported in studies dealing with the connectivity of embryonic cortex grafted into newborn hosts, the density of the connections established between thalamus and graft was systematically weaker than that developed between thalamus and intact cortex (Ebrahimi‐Gaillard et al ., 1994; Roger & Ebrahimi‐Gaillard, 1994; Létang et al ., 1997; Gaillard & Roger, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This study shows that cortical cells removed at E12 from the presumptive parietal area of the telencephalic vesicle and transplanted into the parietal cortex of P0 hosts develop and maintain a substantial set of reciprocal connections with the VB. These findings obtained with early embryonic cortex are in line with those of previous reports describing the existence of thalamic afferents and/or efferents of grafts of E16 embryonic cortex homotopically placed in various cortical areas (reviewed in Ebrahimi‐Gaillard et al ., 1994; Roger & Ebrahimi‐Gaillard, 1994; Létang et al ., 1997; Frappé et al ., 1999, 2001; Gaillard & Roger, 2000). In particular, grafts of E16 parietal cortex placed into the parietal cortex of P0 recipients develop a substantial set of afferent and efferent connections with the host VB (Gaillard & Roger, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors, considered essential by many researchers, is the formation of connections between the host and transplanted tissue. Classically, it has been reported that functional success for frontal cortical transplant following motor cortex lesion depends on trophic action on the host brain and reconstruction of cortical circuitry, which improves the performance of animals in behavioral tests like the T-maze (Labbe et al, 1983;Roger and Ebrahimi-Gaillard, 1994). Moreover, it has been shown that a lesion in the rat frontal cortex produces a deficit in the paw used in reaching tasks (Plumet et al, 1991;Plumet et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic alterations of the axonal wiring, such as those happening in cortical lesions, immediately produce a permanent functional impairment which leads to behavioral deficits and have severe anatomical consequences (Sorensen et al, 1989; Plumet et al, 1993; Gaillard et al, 1998; Riolobos et al, 2001; Chen et al, 2002). Embryonic tissue transplanted into the damaged cortex of adult rats has shown successful survival and establishment of reciprocal connections between the host and grafted tissue (Castro et al, 1988; Xu et al, 1991; Plumet et al, 1993; Roger and Ebrahimi-Gaillard, 1994; Frappe et al, 1999; Chen et al, 2002; Gaillard et al, 2007; Gaillard and Domballe, 2008; Santos-Torres et al, 2009) and has lead to behavioral graft-dependent recovery (Labbe et al, 1983; Fernandez-Ruiz et al, 1991; Plumet et al, 1991; Riolobos et al, 2001; Heredia et al, 2004). Therefore, certain level of adequate axonal wiring seems to be necessary for the reconstruction of cortical circuitry and restoration of lost brain function.…”
Section: Introductionmentioning
confidence: 99%